Photokopolimerisasi monomer akrilat degan kulit kras sapi - Dwi Wahini Nurhajati; Agustin Suraswati; Kadarijah Kadarijah; Made Sumarti (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 1997)
The research on photocopolymerization of acrylate monomer with cow crust hide had object to observe the resulted copolymer onto cow crust hide. Crust hides, saturated with aqueous emulsions containing 25 wt % of n-butyl acrylate (n-BA) or tripropylene glycol diacrylate (TPGDA) were irradiated by cobalt – 60 gamma rays with doses ranges from 5 to 25 kGy. The irradiated hides were washed with water, dried in air and extracted in soxhlet apparatus for 48 hours to remove homopolymer. The highest yield of photocopolymerization of n – butyl acrylate monomer with crust hides was found 17,7878% at dose 25 kGy, and for photocopolymerization of tripropylene glycol diacrylate with crust hides was found 39,4245% at dose 20 kGy. INTISARI Penelitian photokopolymerisasi monomer akrilat dengan kulit kras sapi bertujuan untuk mengetahui banyaknya kopolimer yang dihasilkan didalam kulit kras sapi. Kulit kras yang sudah dijenuhkan dengan emulsi n – butyl akrilat atau tripropilena glikol diakrilat dalam air dengan konsentrasi monomer 25% berat, diiradiasi dengan sinar gamma kobalt – 60 dengan dosis yang bervariasi dari 5 sampai 25 kGy. Kulit yang sudah diradiasi dicuci dengan air, dikeringkan di udara dan diekstraksi dalam peralatan soxhlet selama 48 jam untuk menghilangkan homopolimer. Hasil tertinggi dari photokopolimerisasi monomer n – butyl akrilat dengan kulit dicapai pada dosis 25 kGy yaitu sebesar 17,7878%, dan untuk photokopolimerisasi monomer tripropilena glikol diakrilat dengan kulit dicapai pada dosis 20 kGy sebesar 39,4245%.